(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: During the COVID-19 pandemic, dental treatment was classified as a high-risk profession. As a result, dentists faced significant challenges in providing proper oral health care. In the aftermath of the pandemic, dentists encountered various multifaceted difficulties. This study aimed to assess the post-COVID challenges faced by dentists in Bangladesh. Materials and methods: This cross-sectional study was conducted among 96 dentists of Chittagong Medical College, Dental Unit and Chattagram International Dental College. Data were collected by pre-tested semi-structured questionnaire and face-to-face interview was done. The sampling technique was purposive. The analysis was done by using IBM SPSS version 26 and presented by frequencies, percentages, charts, tests & diagrams. Results: The study found that 57% of dentists closed their practices during the lockdown. Of those, 44% closed due to the complete lockdown, 31% due to safety concerns. Most dentists faced challenges in maintaining a safe environment during the pandemic, especially in avoiding waiting room gatherings (54.2%) and ensuring infection control (46.9%). A majority (89.6%) felt their practices were hampered by the pandemic, with 19.8% always hindered and 69.8% occasionally hindered. Among the dentists, 18.8% faced consistent economic hardship and more than 80%experienced anxiety or stress from practice closures. There were no significant differences in difficulties faced by male and female dentists (p > 0.05). However, there was a significant association between worries about infection and gender (p < 0.05) as well as age, with varying concerns noted across different age groups (p < 0.01). Conclusion: This study explored multidimensional challenges faced by both dentists in post-COVID situations regarding oral healthcare and concluded the specific recommendations that will help our policymakers to take necessary steps to overcome these challenges and will contribute to improving the condition of the oral health sector. Chatt Maa Shi Hosp Med Coll J; Vol.25 (1); January 2026; Page 89-94